Ataxia Telangiectasia: A Case Report (Journal of Shaheed Suhrawardy Medical College, 2017)
Ataxia telangiectasia (AT) is a complex multisystem disorder characterized by progressive neurological impairment, variable immunodeficiency and occulo-cutaneous telangiectasia. Ataxia telangiectasia is a member of chromosomal breakage syndromes and it is caused by a mutation in the ataxia-telangiectasia mutated (ATM) gene. We are reporting an eight year old girl of AT presented with difficulty in walking, frequent fall, trembling of the whole body, difficulty in speech.J Shaheed Suhrawardy Med Coll, June 2014, Vol.6(1); 41-43